Systematic Literature Review: Model Pembelajaran Jigsaw dengan Pendekatan Etnomatematika untuk Meningkatkan Pemahaman Konsep Siswa - Salsabila, Dina; Luthfiana, Maria; Umam Zaid Nugroho, Khathibul (STAI Al-Bahjah, 2025)
The Jigsaw learning model integrated with an ethnomathematics approach provides a substantial contribution to the development of students’ conceptual understanding and higher-order thinking skills. This study reviews 10 relevant articles published between 2020 and 2025 using the Systematic Literature Review (SLR) method. The analysis indicates that incorporating local cultural values into cooperative learning strengthens the contextual foundation of the material and fosters a more dynamic, interactive, and meaning-oriented learning environment. The ethnomathematics-based Jigsaw model has been shown to enhance students’ learning motivation, collaborative abilities, and critical thinking skills. Moreover, students demonstrate improved competence in relating mathematical concepts to cultural practices and real-life situations, resulting in deeper and more applicable understanding, Through structured group work and clearly defined task distribution, this approach supports balanced development of students’ social and cognitive abilities. Learners gain not only procedural knowledge but also an awareness of the relevance of mathematics in daily life. Culturally grounded learning encourages students to view mathematics as an integral part of their cultural identity rather than as abstract symbols. The findings of this review affirm that the integration of ethnomathematics within the Jigsaw model facilitates authentic, experience-based learning that is adaptable to local contexts. Overall, this approach provides an alternative instructional strategy for mathematics education that is more contextual, collaborative, and meaningful for students.